Stimulating Domestic Demand as a Key Factor of Economic Growth - Ershov, Mikhail V.; Tanasova, Anna S.; Sokolova, Elena Yu. (Economy of Regions, 2021)
World economy shows a high level of uncertainty. There are considerable risks of economic slowdown and stock market collapse. For many years, the Russian economy has been dependent on external factors. Recently, when anti-Russian sanctions are imposed, it is particularly important to find internal sources of growth, including domestic demand as the most significant factor. However, environment for the development of the Russian economy remains unfavourable due to high interest rates, volatile exchange rate, increasing tax rates, and ambiguous economic policy. Based on the analysis of regional statistics (including some regions of the Central Federal District), we confirmed the weak relationship between investments and gross regional product (GRP) revealed by other scientists. This may be the result of poor investment efficiency and its low multiplier effect. In this situation, the right choice of sectors with high multipliers and investment efficiency creates the potential for increasing domestic demand. Simultaneously, mechanisms for the expansion of resources ensuring regional economic growth play an important role. In this regard, we developed approaches aimed at the creation of conditions for the expansion of regional financial resources to support economic activity, domestic demand and economy in general, considering a social aspect of these processes. Some of the proposed mechanisms stimulate the participation of banks in financing economic processes, federal or regional bond issuance (the Bank of Russia would be the main buyer), etc. These proposals consider the experience of other countries in stimulating economic growth, including at the regional level. Financial regulators and relevant regional agencies can use the research results for developing economic policies.